1987
DOI: 10.1073/pnas.84.19.6899
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of the epidermal growth factor receptor gene in malignant gliomas is invariably associated with gene amplification.

Abstract: Primary malignant gliomas from 63 patients were analyzed to determine the relationship between amplification of the gene encoding the epidermal growth factor receptor (EGFR) and expression of the corresponding mRNA. Twenty-four tumors were found to have amplified the EGFR gene and amplification of other genes occurred in three additional tumors. Hybridization with synthetic RNA probes was used to quantitate mRNA levels in situ. All 24 tumors with amplification of the EGFR gene had high levels of expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
387
1
6

Year Published

1990
1990
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 730 publications
(405 citation statements)
references
References 34 publications
11
387
1
6
Order By: Relevance
“…As a result of multistep tumor progression, malignant gliomas are genetically heterogeneous tumors (Louis and Gusella, 1995). The most consistent genetic alterations identi®ed to date include p53 abnormalities (Bogler et al, 1995;Rasheed et al, 1994), alterations in the p16/CDKN2/pRb pathway (Ueki et al, 1996) and EGFR gene ampli®cation and rearrangement (Libermann et al, 1985;Wong et al, 1987;Humphrey et al, 1988;Bigner et al, 1990). Levels of EGFR in gliomas are proportional to tumor invasiveness (Lund-Johansen et al, 1990) and overexpression of wild type EGFR has been shown to induce ligand-dependent cellular transformation of astrocytes, indicating a direct role for the receptor in oncogenesis (Frisa et al, 1996;O'Rourke et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of multistep tumor progression, malignant gliomas are genetically heterogeneous tumors (Louis and Gusella, 1995). The most consistent genetic alterations identi®ed to date include p53 abnormalities (Bogler et al, 1995;Rasheed et al, 1994), alterations in the p16/CDKN2/pRb pathway (Ueki et al, 1996) and EGFR gene ampli®cation and rearrangement (Libermann et al, 1985;Wong et al, 1987;Humphrey et al, 1988;Bigner et al, 1990). Levels of EGFR in gliomas are proportional to tumor invasiveness (Lund-Johansen et al, 1990) and overexpression of wild type EGFR has been shown to induce ligand-dependent cellular transformation of astrocytes, indicating a direct role for the receptor in oncogenesis (Frisa et al, 1996;O'Rourke et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…EGFR ampli®cation occurs in up to 50% of malignant gliomas with gene rearrangement in approximately one-half of those tumors leading to frequent co-expression of both wild type and mutant receptors (Libermann et al, 1985;Wong et al, 1987;Humphrey et al, 1988;Bigner et al, 1990;Ekstrand et al, 1991). Expression of these EGFR mutants has been reported to be associated with a poor prognosis (Schlegel et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR) gene (protooncogene of v-erbB) is amplified and overexpressed in about 40% of cases of glioblastoma, the major malignant tumour of human brain Wong et al, 1987;Humphrey et al, 1988). This amplification is frequently correlated with structural rearrangement of EGFR, resulting in in-frame deletion mutations in the extracellular domains (Humphrey et al, 1988(Humphrey et al, , 1991Yamazaki et al, 1988Yamazaki et al, , 1990Bigner et al, 1990;Wong et al, 1992).…”
mentioning
confidence: 99%
“…In malignant gliomata, over-expression of the EGFR protein appears to be associated with gene amplification (Wong et al, 1987). In culture, the growth of glial tumour cells can be stimulated by EGF (Frappaz et al, 1988) and antibodies against the EGFR can inhibit such stimulation (Werner et al, 1988).…”
mentioning
confidence: 99%